Australia : Financial Sector Assessment Program-Technical Note-Stress Testing the Banking Sector and Systemic Risk Analysis. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This technical note describes the financial stability analysis undertaken as part of the Financial Sector Assessment Program that primarily focuses on assessing the resilience of the banking system. Bank solvency appears relatively resilient to stress, although liquidity stress tests reveal some vulnerabilities given continued reliance on wholesale funding. The systemic risk analysis reveals a low degree of interconnectedness between the largest Australian banks and their global counterparts. However, the cross-border and interbank exposures data corroborates the systemic importance of the four largest banks and the view that the Australian banks are particularly vulnerable to external funding shocks. Cross-border analysis using country-level and individual bank-level supervisory data corroborates the view that the Australian banks are particularly vulnerable to external funding shocks given their dependence on wholesale funding from overseas. Policy recommendations made in the note include that additional investment in data and analytical tools would strengthen financial supervision and systemic risk oversight.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet